KATTA URADARYO HAVZASINING LANDSHATLARGA TASIRI - Xosiyat , Sapayeva (Scientific Impulse, 2023)
A body of water is a source of slow flowing or non — flowing water that is generated from the accumulation of water naturally or artificially in natural or artificial low or deep areas of the Earth's surface, or, if not, blocking the waterway and building a dam. The body of water is divided into permanent or seasonal (appearing in the Seryogin years) species. The permanent body of Water includes oceans, seas, rivers, lakes, natural reservoirs, Jills, ditches and other. A seasonal (temporary) body of water consists of artificial reservoirs, channels, pools, etc. For example, the Aral Sea, Amudarya, Syrdarya, Chirchik rivers on the territory of Uzbekistan are natural water bodies, Tashkent sea, livestock reservoir, Andijan reservoir and other artificial water bodies.